2013
DOI: 10.1371/journal.pone.0073517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Patient Acceptable Symptom State (PASS) in Italian Patients Affected by Systemic Lupus Erythematosus: Association with Disease Activity Indices

Abstract: ObjectivesThe aim of this study was to evaluate the discriminant capability of the patient acceptable symptom state (PASS) according to disease activity, in a cohort of Italian patients affected by systemic Lupus erythematosus (SLE).MethodsConsecutive SLE patients were enrolled. At each visit, the patients underwent a complete physical examination and the clinical/laboratory data were collected in a standardized, computerized, and electronically-filled form. The evaluation of serum complement C3 and C4 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In keeping with other validation studies, the result of this analysis suggested the ability of LupusQoL in capturing different levels of disease activity, unlike a generic index such as SF-36 [47]. In another study, the patient acceptable symptoms state (PASS), a tool used to evaluated patients' outcome, was found associated with disease activity [48]. PASS is a singlequestion outcome tool to evaluate the level of symptoms at which patients consider themselves well.…”
Section: Correlation Between Disease Activity Chronic Damage and Quasupporting
confidence: 68%
See 1 more Smart Citation
“…In keeping with other validation studies, the result of this analysis suggested the ability of LupusQoL in capturing different levels of disease activity, unlike a generic index such as SF-36 [47]. In another study, the patient acceptable symptoms state (PASS), a tool used to evaluated patients' outcome, was found associated with disease activity [48]. PASS is a singlequestion outcome tool to evaluate the level of symptoms at which patients consider themselves well.…”
Section: Correlation Between Disease Activity Chronic Damage and Quasupporting
confidence: 68%
“…PASS is a singlequestion outcome tool to evaluate the level of symptoms at which patients consider themselves well. This tool has been used in a large cohort of SLE patients, identifying significantly lower levels of SLEDAI-2K and ECLAM in subjects considering their condition acceptable [48]. The study suggested the ability of PASS in discriminating patients affected by SLE with different levels of disease activity [48].…”
Section: Correlation Between Disease Activity Chronic Damage and Quamentioning
confidence: 99%
“…The health-related quality of life (HRQoL) of SLE patients can be evaluated by administering questionnaires such as the Short-form 36 (SF-36) [56], and the Patient Acceptable Symptom State (PASS) a simple questionnaire used to assess well-being in various rheumatic diseases including SLE [57].…”
Section: Sle and Fibromyalgiamentioning
confidence: 99%
“…PASS is a single-question outcome tool to evaluate the level of symptoms at which patients consider themselves well, previously used to assess patients with inflammatory arthropathies and osteoarthritis, demonstrating a significant association with disease activity [50,51]. PASS question has been administered to 165 consecutive SLE patients demonstrating an acceptable clinical state in 80% of subjects [52]. In addition, PASS seems to be able to discriminate patients with different disease activity, as shown by the significantly lower mean SLEDAI-2K and ECLAM values in patients with an acceptable status compared with the others; moreover, active musculoskeletal involvement seemed to influence the status acceptability [52].…”
Section: Quality Of Lifementioning
confidence: 99%
“…PASS question has been administered to 165 consecutive SLE patients demonstrating an acceptable clinical state in 80% of subjects [52]. In addition, PASS seems to be able to discriminate patients with different disease activity, as shown by the significantly lower mean SLEDAI-2K and ECLAM values in patients with an acceptable status compared with the others; moreover, active musculoskeletal involvement seemed to influence the status acceptability [52].…”
Section: Quality Of Lifementioning
confidence: 99%